Federal state financial relations : theories and principles - Rao, Hemlata (New Delhi, 1994)
This book examines the theoretical basis and economic rationale of the various tools of federal fiscal transfers such as tax devolution grants and grants-in-aid in the context of India.
Keywords: Fiscal relations